Intrapreneurship and regional development in the South East of Ireland. Issue 1 (31st December 2022) - van Egeraat, Chris; Curran, Declan
ABSTRACT: Intrapreneurship is known to play an important role in enhancing innovation and competitiveness within firms. However, there remains a dearth of literature on the workings of intrapreneurship at the regional level. Based on a qualitative analysis of intrapreneurship in the South East Region of Ireland, this paper explores the link between intrapreneurship and regional development. It makes several contributions that further the understanding of intrapreneurship at the regional level: (1) we detail the manner in which intrapreneurship emerges in distinct corporate contexts; (2) we identify the main barriers and challenges to intrapreneurship in these different contexts; and (3) we provide evidence that sets out the relative importance of the two key routes through which intrapreneurship stimulates regional development: firm growth and new firm formation.